2005
DOI: 10.1300/j013v41n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Social Support as Predictors of Health, Psychological Well-Being and Life Satisfaction Among Dutch Male and Female Dual-Earners

Abstract: We examined whether gender differences in health, psychological well-being, and life satisfaction, can be explained by effects of work-related and nonwork-related sources of social support. The sample consisted of 459 men and women from dual earner families. Men report better health and psychological well-being than women, whereas women report higher life satisfaction than men. Contrary to our expectations, women receive more social support from colleagues than men, while men and women equally receive support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 37 publications
4
23
0
1
Order By: Relevance
“…They also scored lower in self-esteem than men. These characteristics have often been reported in other studies researching women across professions (Daalen et al 2005;Grossi et al 2003;Scherer et al 1990;Voltmer and Spahn 2009). Concordant with these findings, resignation tendencies were the only dimension with no significant differences between women across the professional groups investigated here.…”
Section: Discussionsupporting
confidence: 75%
“…They also scored lower in self-esteem than men. These characteristics have often been reported in other studies researching women across professions (Daalen et al 2005;Grossi et al 2003;Scherer et al 1990;Voltmer and Spahn 2009). Concordant with these findings, resignation tendencies were the only dimension with no significant differences between women across the professional groups investigated here.…”
Section: Discussionsupporting
confidence: 75%
“…Together, our analyses of family and friend relationships suggest that among those with a history of SUD, both men and women face family situations that are problematic (although the specific dimensions of problematic family relations differ), and consistent with other research, that women place a stronger reliance on friend networks to meet emotional needs than men (Colarossi & Eccles, 2003;Siebert, Mutran, & Reitzes, 1999;van Daalen, Sanders, & Willemsen, 2005). While these putative distinctions require replication and more detailed examination, it is possible that they reflect real differences in seeking and receiving support.…”
Section: Sex Differences In Family Relationships Of Drug Dependent Lasupporting
confidence: 80%
“…Much of the research has been focused on definitions of social support and social networks, in addition to the identification of essential, active network factors such as size, quality, availability, density, reciprocity and utilization, how networks function and to what degree they facilitate service utilization and support recovery. The attempts at defining social support and social networks illustrate a diverse set of approaches, and one can hardly imagine any simple instrument being developed that could accurately measure social support 1 (Felton and Shinn 1992, van Daalen et al 2005, Tello et al 2005. Some researchers have suggested that larger meta-analyses will identify the central factors (Haber et al 2007), while others have underscored the complexity in both environmental resources and individual needs (O'Reilly 1988, Buchanan 1995, Hardiman 2004, Williams et al 2004, Dorvil et al 2005, Cox 2006, Östberg 2007 and suggested that the subjective and objective aspects of social support and social networks can best be approached by the use of qualitative methods (Williams et al 2004).…”
Section: Introductionmentioning
confidence: 99%